Intelligent Blind-User Navigational Device Utilizing Image Processing - Manikandan, J; S, Aparna; R, Swathi; N, Sneha S (IRO Journal on Sustainable Wireless Systems, 2023)
There are many thousands of blind people in the world who frequently require support. Since the white cane has long been known as an essential component of blind people’s navigation, efforts have been made to enhance it by adding new sensors. Blind people are relatively comfortable inside their homes because they can pinpoint where things are, but in the outside world, as the objects are in motion, they face difficulties in locating the objects without an assistance. The research put forth strives to develop a sound navigation and range system for blind people. A real-time obstacle identification has been accomplished using ultrasonic sensors. In order to create a safe path for navigation to a destination, image processing in real-time is used for providing the blind person’s perception of the size and distance of the obstacle utilizing raspberry pi for object detection. The suggested method makes use of a camera for recording the video sequence of surroundings, which it subsequently processes using a vocal input from a person who is visually impaired. It takes the location data while taking the (GPS) module for outdoor use. The location detail gathered is transported to the cloud.